Quality of the forage apparently consumed by beef calves in natural grassland under fertilization and oversown with cool season forage species - Elejalde, Denise Adelaide Gomes; Nabinger, Carlos; Pascual, Mónica Graciela Cadenazzi; Ferreira, Eduardo Tonet; Missio, Regis Luis [UNESP]; Kunrath, Taise Robinson; Devincenzi, Thais; Cardoso, Raquel Rolim (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate the chemical composition of the forage apparently consumed by steers in a natural grassland on region of Campanha, in Rio Grande do Sul, Brazil, subjected or not to different inputs: NP - natural pasture without inputs; FNP - fertilized natural pasture and INP - improved natural grassland with fertilization and over-seeded with cultivated winter species. Three Angus steers testers and a variable number of regulator animals per experimental unit were utilized in order to maintain 13 kg of DM/100 kg of live weight (LW) as forage allowance. One time at each season, hand plucking samples were performed along the daily grazing time simulating forage harvested by the animals. The collected samples after drying and grind were submitted to chemical analysis to determine the forage quality. Except in winter and spring, the values of neutral detergent fiber were higher than the critical value of 550 g/kg of DM, which could limit forage intake, demonstrating that the values of forage on offer provided (15.6; 13.7; 13.5; 15.8 kg of DM/100 kg of LW/day in summer, autumn, winter and spring, respectively) were not restrictive to intake. The oversowing of winter cultivated species or fertilization positively alter the degradable fiber content. The seasons had marked influence on the chemical composition of forage apparently consumed; positively increasing some fractions of forage chemical composition in the seasons in which native or cultivated winter species increased their participation. The forage chemical composition is the determining factor in animal performance in natural pasture.
Keywords: average daily weight gain; gas in vitro digestibility; neutral detergent fiber corrected for ash and protein; total digestible nutrients